-5(x-3)+2x=6

Simple and best practice solution for -5(x-3)+2x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-3)+2x=6 equation:


Simplifying
-5(x + -3) + 2x = 6

Reorder the terms:
-5(-3 + x) + 2x = 6
(-3 * -5 + x * -5) + 2x = 6
(15 + -5x) + 2x = 6

Combine like terms: -5x + 2x = -3x
15 + -3x = 6

Solving
15 + -3x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -3x = 6 + -15

Combine like terms: 15 + -15 = 0
0 + -3x = 6 + -15
-3x = 6 + -15

Combine like terms: 6 + -15 = -9
-3x = -9

Divide each side by '-3'.
x = 3

Simplifying
x = 3

See similar equations:

| 14(2f)=7(f-2) | | 9y-(11)-(5y)=-25 | | -53-2i=-I+73 | | y/11=17 | | 6x+4=70 | | 2.4(3.1x+4.9)=75.9+0.87 | | m(m-3)=54 | | 5m-7= | | -4-(1-5)-4x-4= | | x/8=-6 | | 7x+17=3x+1 | | x/8=-7 | | 9y-11-5y=-25 | | 10x^2-2x-6=0 | | -6s+-15=15 | | 3=.33-2b | | 3k^2=-12-20k | | 3a-4a=9-4a | | -4-(1-5)=-4x-4 | | 9+9=97+x | | 9(x+1)-3x=2(3x+1)-4 | | 4(s+1)=12(s+3) | | 18-4x=-36 | | 10x+5(x-3)=15 | | 4e^16x=14 | | 6x-12=2x+36 | | -24y-42=18 | | s+14=17-5s | | 7n^2+2=9n | | 8c+30=10c | | -x-62=136-12x | | 42=7j-28 |

Equations solver categories